Ethical questions in dentistry, second edition - Rule, James T.; Robert M. Veatch (Chicago, Illinois : Quintessence Publishing Co, Inc., 2019)
Updated to reflect the current ethical climate, this book presents clinical practice cases in which arguments can be made for differing courses of action or in which the obligations of the professional are in conflict; the reader is asked to determine the ethically correct response to such conflicts. In this revised edition, detailed background material has been added to many of the cases to foster more well-reasoned ethical decision making. In addition, cases on sexual harassment and advertising have been introduced, and those on financial and HIV issues have been updated. An entirely new chapter on the structure and obligations of the various professions has been added. This book will continue to be of value to members of the dental profession and is now better suited to the needs of ethics courses for dental students.
Ethical questions in dentistry, second edition -- Table of Contents -- Cases -- Preface to the Second Edition -- Preface to the First Edition -- Acknowledgments -- Introduction -- Part I. Ethical Questions: Theory and Principles -- Chapter 1: An Overview of Ethicsin Dentistry -- Chapter 2: The Structure of Professions and the Responsibilities of Professionals -- Chapter 3: Basic Ethical Theory -- Chapter 4: Ethical Principles -- Chapter 5: Format for Resolving Ethical Questions -- Part II. General Principles in Dental Ethics -- Chapter 6: Doing Good and Avoiding Harm -- Chapter 7: Fidelity: Obligations of Trust and Confidentiality -- Chapter 8: Autonomy and Informed Consent -- Chapter 9: Dealing Honestly with Patients -- Chapter 10: Justice in Dentistry -- Part III Case Studies of Special Problems -- Chapter 11: Ethical Concerns in Schools of Dentistry -- Chapter 12: Ethical Issues in Third-Party Financing -- Chapter 13: Ethical Issues Involving HIV and Other Bloodborne Diseases -- Chapter 14: Incompetent, Dishonest, and Impaired Professionals -- Appendix 1. Codes of Medical Ethics -- Appendix 2. Informed Consent -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: Ethics, Dental; Case Reports